2022
DOI: 10.26907/esd.17.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Digital Competencies and Digital Literacy in the 21st Century: A Survey of Studies

Abstract: The development of digital competencies and digital literacy in the 21st century is one of the most urgent in the theory and practice of modern education. The need for an understanding of the analysis of scientific knowledge on this issue is confirmed by the high demand for digital competencies of specialists in the labor market. The paper organizes and presents publication trends in the field of human digital abilities, with an emphasis on in-depth study of topics in higher education. Reviews and analytical w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…A er all, when an adult overly controls the activities of a preschooler and does not give him/her the opportunity to take initiative, make decisions, or independently follow a plan, then the adult, as it were, takes on the role of the child's EF. Second, there is a lack of scienti cally proven evidence on how to nd and choose high-quality educational apps (Aleksandraki & Zaranis, 2023;Belolutskaya et al, 2023;Papadakis et al, 2021;Pesha, 2022). A study by Papadakis et al (2022) showed that parents prefer to download free apps for children.…”
Section: Ef and Joint Media Engagement Of Preschoolers And Their Parentsmentioning
confidence: 99%
“…A er all, when an adult overly controls the activities of a preschooler and does not give him/her the opportunity to take initiative, make decisions, or independently follow a plan, then the adult, as it were, takes on the role of the child's EF. Second, there is a lack of scienti cally proven evidence on how to nd and choose high-quality educational apps (Aleksandraki & Zaranis, 2023;Belolutskaya et al, 2023;Papadakis et al, 2021;Pesha, 2022). A study by Papadakis et al (2022) showed that parents prefer to download free apps for children.…”
Section: Ef and Joint Media Engagement Of Preschoolers And Their Parentsmentioning
confidence: 99%
“…Переход от традиционной модели массового обучения, предполагающей единый учебный план для всех обучающихся по образовательной программе и ориентированной на «среднего» студента, способного освоить этот план, к индивидуализированному обучению с активным участием обучающихся в формировании своей траектории в рамках выбранной образовательной программы становится приоритетом в развитии высшего образования (Daineko et al, 2021). Благодаря широкому внедрению цифровых технологий возникают технологические предпосылки для управления обучением десятков тысяч студентов, каждый из которых следует индивидуальному учебному плану, включающему помимо обязательных дисциплин широкий спектр вариативных модулей под разные профессиональные задачи (Pesha, 2022). Индивидуализация образовательной траектории позволяет каждому студенту получить уникальный набор компетенций, а также повысить конкурентоспособность на рынке труда.…”
Section: Introductionunclassified
“…The advancement of technology has also led to an increase in the number of educational possibilities available. The limits of space, which were formerly imposed on educational activities because they had to take place in a certain location, have been lifted as a result of mobile technologies (Kryukova et at., 2022;Pesha, 2022;Qarkaxhja et al, 2022). In addition, learners can be presented with potentially hazardous and expensive learning scenarios in a more secure and cost-effective manner using virtual realities.…”
Section: Introductionmentioning
confidence: 99%